How important are Russia's external economic links? - Iikka Korhonen; Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
In this note, we review recent data concerning Russia's economic integration with other countries. We first analyze the general picture of Russia's economic integration with the rest of the world and the importance of foreign economic relations for the country. We then turn to China, an increasingly significant economic partner for Russia. The European Union remains Russia's most important trading partner and is by far the most important source of foreign direct investment to Russia as well as sources of other financing. China's importance to Russia has also increased, especially with respect to merchandise trade.
urn:nbn:fi:bof-202202171067
Keywords: 330; Russia; economic integration; trade; investment